Equality, Responsibility, and Culture: A Comment on Alan Patten’s Equal Recognition - Quong, Jonathan (Les ateliers de l'éthique / The Ethics Forum, 2015)
Alan Patten presents his account of minority rights as broadly continuous with Ronald Dworkin’s theory of equality of resources. This paper challenges this claim. I argue that, contra Patten, Dworkin’s theory does not provide a basis to offer accommodations or minority rights, as a matter of justice, to some citizens who find themselves at a relative disadvantage in pursuing their plans of life after voluntarily changing their cultural or religious commitments.